Which expression is equivalent to 1/2 (2+ 3x – 6)?
3x - 5
3/2x - 5
3x – 4
3/2x - 2
The Answer Is B
Umm, That's A lot Of Homework...
Answer:
The answer is C.
Step-by-step explanation:
m=y²-y¹/x²-x¹
m=(-12)-13/2-7
m=-25/-5
m=5
Find the common denominator of 6 and 4.
6: 6, 12...
4: 8, 12...
We can use 12 for this example.
5/6 to ?/12.
12 / 6 = 2, therefore do 5 x 2.
5 x 2 = 10. 10/12.
1/4 to ?/12.
12 / 4 = 3, therefore do 3 x 1.
3 x 1 = 3. 3/12.
13/12. 1 1/12.
I believe you ran out of space or didn't put answer D. I researched this question and concluded that the other choice is 1 and 1/12.
The answer is 1 and 1/12.